Measuring the urgency of tax administration reform in Indonesia - Purba, Andi Derma; Salomo, Roy Valiant (International research journal of management, IT and social sciences, 2024)
This research aims to explore the latest developments in taxation and describe why Indonesia must implement tax reform. The primary focus is on the state revenue generated by the tax sector over the last ten years, tax ratios, and the extent of the state's losses due to tax abuse in Southeast Asia. The research uses a constructive philosophy and paradigm with a qualitative approach. It employs explanatory research, with library research as a data collection technique. The findings indicate that significant measures are required to reform Indonesia's tax administration to increase state revenues from taxes, raise the tax ratio, and reduce the amount of state losses due to tax abuse. The complex tax administration system leads to tax avoidance and abuse, reducing the state's revenue and causing the tax ratio to be low. The government needs to organize the workings of the tax system using the principles of equality, simplicity, and justice. The research results are addressed to the government as regulators and policymakers, as well as to taxpayers and the public as policy implementers. Taxpayers and the public can comply with their tax obligations without hesitation because the tax system is strong, credible, and accountable.